Geothermal Energy and Greenhouse Gas Emissions: A Systematic Review - Hackett, Sidney; de Witt, Magnus (Sustainability & Circularity NOW, 2026)
This systematic review evaluates life cycle greenhouse gas emissions from geothermal electricity generation, with a focus on hydrothermal flash, hydrothermal binary, and enhanced geothermal systems. By screening 169 studies published since 2017, 24 met the inclusion criteria and were analyzed alongside Pre-2017 benchmarks. Results indicate median life cycle emissions of 43 g CO2 eq/kWh for hydrothermal flash, 36 g CO2 eq/kWh for enhanced geothermal, and 30 g CO2 eq/kWh for hydrothermal binary. Compared with fossil fuels, these values remain substantially lower, underscoring the role of geothermal in low-carbon energy transitions. Evidence suggests that emissions are declining during the construction phase due to advances in drilling efficiency and modular plant design, while operational emissions remain stable, reflecting the limited deployment of carbon capture. End-of-life recycling varies between technologies. These findings highlight geothermal energy’s capacity to support resilient, circular, and sustainable power systems.
Keywords: Geothermal Energy; Greenhouse Gas Emissions; Life Cycle Assessment; Circular Economy; Energy Transition